2021
DOI: 10.1002/app.50531
|View full text |Cite
|
Sign up to set email alerts
|

Aramid fiber reinforcedEPDMmicrocellular foams: Influence of the aramid fiber content on rheological behavior, mechanical properties, thermal properties, and cellular structure

Abstract: In this paper, aramid fiber (AF)/ethylene‐propylene‐diene monomer (EPDM) microcellular foams added with different content of AF are prepared by the supercritical foaming method. The effect of the AF content on the rheological behavior, mechanical properties, thermal properties and cellular structure of the AF/EPDM microcellular foams has been systematically studied. The research illustrates that compared with pure EPDM, the AF/EPDM matrix has greater viscosity and modulus, which is conducive to reduce the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The second decomposition step (490–650°C) generally was due to some homolytic cleavages of amide bonds and the breakings of linking bonds between the amide group and the benzene rings at meta-positions. 37 Moreover, small units of aryl nitriles were also mainly yielded during the second thermal disruption step, as well as for some other volatile matters. Simultaneously, some cross-linking reactions also proceeded among the generated intermediates to produce various condensed aromatic compounds, as described in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second decomposition step (490–650°C) generally was due to some homolytic cleavages of amide bonds and the breakings of linking bonds between the amide group and the benzene rings at meta-positions. 37 Moreover, small units of aryl nitriles were also mainly yielded during the second thermal disruption step, as well as for some other volatile matters. Simultaneously, some cross-linking reactions also proceeded among the generated intermediates to produce various condensed aromatic compounds, as described in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the first decomposition step for the aramid fiber samples was usually ascribed to the disruption of the backbone of the fiber macro-chains via some heterolytic breakings of the amide bonds, accompanied by the releases of some low molecular weight matters, such as carboxylic acids, primary amines, and so on. 25,37 Particularly, some volatile fragments were produced during the first decomposition step and resulted in the mass loss of fiber substrate. Furthermore, various cross-linking reactions among the pyrolyzed intermediates usually also occurred to form some new compounds during the first decomposition step.…”
Section: Thermal Decomposition Behavior and Kineticsmentioning
confidence: 99%
“…The cellular distribution of the fractured face was analyzed using Nano Measurer software. The cell density (N f ) was calculated according to the following equation: [35]…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, peroxide curing system has been proven to be useful for the co-vulcanization of HNBR and EPDM. [11][12][13][14][15] According to M.S.Loo, the fatigue properties of natural rubber were influenced strongly by the biodiesel environment, and the service life of expanded rubber was shorter than that of unexpanded rubber. 16 The research of Balasooriya studied the effect of swelling on the tribological properties of HNBR in different liquid environments, 17 which found that mechanical properties deteriorated in the swelling state and recovered after de-swelling.…”
Section: Introductionmentioning
confidence: 99%